A Z-scheme concept of V2O5 and boron doped G-C3N4 nanocomposite for the photodegration of diclofenac sodium - Oliveros, April N.
A Z-scheme concept was conducted through the synthesis of V2O5 and Boron doped g-C3N4. V2O5 was synthesized by calcination at 450 degree celsius at 3 h of NH4VO3 and C6H307 (1:3 mol ratio) mixture. The g-C3N4 was produced by poly-condensation of Urea at 550°C for 4 h. Boron doped g-C3N4 was prepared at 420°C for 2 h with ramp of 5°C min-1. Final composite was prepared through calcination at 300°C for 30 min of V2O5 and Boron doped g-C3N4 mixture. Application was carried out by preparing Diclofenac Sodium (DCF) solution as pollutant. DCF solution and nanocomposite heterogeneous mixture was subjected to photoreactor and sampling was conducted per determined time interval in 45 min adsorption time and 120 min running time. Different variations were conducted such as varying V2O5-BCN loading and DCF initial concentration, initial pH concentration of DCF, introduction of anions and adsorption isotherm. Determination of sample concentration was conducted through high precision liquid chromatography (HPLC Waters 2487). A 100 % removal of DCF10 was achieved with the photocatalytic composite of 50:50 ratio of V2O5-5BCN in less than 120 min while optimum photocatalytic performance was achieved with 2.0 g L-1 loading with initial DCF solution at 5.0 mg L-1 and pH 9. Also, the V205-BCN nanocomposite proved its recyclability and stability after a series of runs and a mechanism has been proposed on the photocatalytic performance of V2O5-BCN nanocomposi